2010
DOI: 10.1021/ic102178d
|View full text |Cite
|
Sign up to set email alerts
|

Structural Principles of Semiconducting Group 14 Clathrate Frameworks

Abstract: We have performed a comprehensive theoretical investigation of the structural principles of semiconducting clathrate frameworks composed of the Group 14 elements carbon, silicon, germanium, and tin. We have investigated the basic clathrate frameworks, together with their polytypes, intergrowth clathrate frameworks, and extended frameworks based on larger icosahedral building blocks. Quantum chemical calculations with the PBE0 hybrid density functional method provided a clear overview of the structural trends a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
158
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 125 publications
(172 citation statements)
references
References 55 publications
14
158
0
Order By: Relevance
“…Recently, Si based clathrates have drawn attention for photovoltaic applications as a result of their tunable quasi-direct band gap in the range needed for optimal performance according to the Shockley-Queisser (SQ) limit. [21][22][23][24] Si-based clathrates without guest atoms in the cages are neutral, and thus they are intrinsic semiconductors. The guest-free low density phases are metastable at ambient conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Si based clathrates have drawn attention for photovoltaic applications as a result of their tunable quasi-direct band gap in the range needed for optimal performance according to the Shockley-Queisser (SQ) limit. [21][22][23][24] Si-based clathrates without guest atoms in the cages are neutral, and thus they are intrinsic semiconductors. The guest-free low density phases are metastable at ambient conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, while the clathrate-II framework is the energetically most stable among all empty group 14 clathrate frameworks, the noble gas adsorption could be energetically even more favourable for some other clathrate frameworks with different constituent cages. [11] Concerning the applied theoretical methods, the adsorption energy trends obtained at the LMP2 and DFT-B3LYP-D3 levels of theory are generally in good agreement, the only cases of qualitative disagreement being Ar 24 [Ge 136 ] and Kr 24 [Ge 136 ], where LMP2 predicts adsorption to be favourable by a small margin, while DFT-B3LYP-D3 predicts the adsorption to be unfavourable. Also for Kr 24 [Si 136 ], where the adsorption is clearly unfavourable with both methods, the quantitative difference of the adsorption energies is rather large.…”
Section: Resultsmentioning
confidence: 94%
“…In the following comparisons, the relative energies of the empty clathrate-II frameworks with respect to the bulk α-phases have been obtained at the DFT-PBE0/SVP level of theory, and they are in good agreement with previous theoretical studies. [11] In the case of Xe 24 [Sn 136 ], the LMP2 adsorption energy of -52 kJ/mol/guest is equivalent to -1248 kJ/mol/unit cell or -9.2 kJ/mol/Sn atom. Considering that the hypothetical guest-free Sn clathrate-II framework is only 2.6 kJ/mol/Sn less stable than the diamond-like α-Sn, the additional stabilization resulting from the noble gas adsorption is very significant.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…All quantum chemical calculations for the polymers were carried out using the CRYSTAL09 program package [50] with a hybrid DFT functional after Perdew, Burke, and Ernzerhof (DFT-PBE0) [51,52]. For silicon, a modified split-valence + polarization (SVP) basis set [53] was applied. The shrinking factor (SHRINK) for generating the Monkhorst-Packtype grid of k points in the reciprocal space was set to 4, resulting in three k-points in the irreducible Further, it was shown that such clusters can serve as seed crystals for the synthesis of Si nanoparticles and nanoscale materials [45,46].…”
Section: Computational Detailsmentioning
confidence: 99%